Against Supersessionist Thinking: Old and New, Jews and Postcolonialism, the Ghetto and Diaspora. (30th August 2017) - Cheyette, Bryan
Abstract: This essay focuses on the liberatory possibilities and political and disciplinary difficulties of bringing together Jewish and postcolonial studies. It begins and ends with Adorno's critique of "actionism" in order to see what is lost when the clarity and certainty of political action is privileged over scholarly nuance and complexity ("praxis" over "theory"). This loss is surveyed through a set of related binaries (supersessionism, foundationalism, and disciplinarity), which, it is contended, reduces critical thinking to polemic and makes it all but impossible to explore interconnected Jewish and postcolonial histories. The argument is illustrated with reference to postcolonial literature and by examining the disciplining of postcolonial and memory studies in relation to the Holocaust. A way out of the binary impasse, it is suggested, is to utilize as "traveling concepts" transcultural and transnational histories (such as "diaspora" and "ghetto") that Jewish and postcolonial studies have in common.